Model Pemilihan Penyedia Jasa Trucking Prioritas Dalam Proses Pengiriman Barang Impor Menggunakan Metode Topsis Di PT IFB Indonesia - Kurniati, Sari Amaliya; Chamsudi, Danie Hayam Mada; Firmansyah, Iqbal (Institut Transportasi dan Logistik Trisakti, 2023)
The increasing activity of shipping goods from abroad and from within the country makes freight forwarding service companies have an important role in these activities. PT. IFB Indonesia, which is a freight forwarding company, is synonymous with cooperation involvement with other logistics service companies to help the process of shipping goods, one of which is cooperation with trucking vendors. The performance of trucking vendors in the process of shipping goods has a great influence on freight forwarding companies. This requires PT. IFB Indonesia as a freight forwarding service company needs to carry out priority trucking vendor selection activities. This research aims to identify and analyze the criteria used in the process of selecting priority trucking vendors. To analyze the selection of priority trucking vendors in PT. IFB Indonesia used the TOPSIS method. The criteria used as assessment materials are price, availability, and reliability criteria. The application of the TOPSIS method will provide assessment results from each criterion for each trucking vendor, so as to provide trucking vendor answers with the best assessment that can be used as a priority choice. The selection of priority trucking vendors is carried out by giving importance to each criterion. The results of the analysis using the TOPSIS method showed the HCC company with a score of 1 as the first rank. Meanwhile, the last rank is the MBS company with a score of 0,20753059.